2010
DOI: 10.3174/ajnr.a2014
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Aneurysms of the Distal Segment of the Posterior Inferior Cerebellar Arteries: Clinical Presentation and Management

Abstract: BACKGROUND AND PURPOSE:Dissecting aneurysms of the distal segment of the PICA are rare. The purpose of this study was to evaluate the clinical presentations, imaging features, treatment options, and clinical outcomes of dissecting PICA aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 29 publications
1
27
0
1
Order By: Relevance
“…Recently, there are lots of reports regarding the interventional therapy of the artery aneurysms (including proximal and distal), all of which are considered to be safe and effective. All the incidences of interventional-related complications are below 10% and there is no report of injury of lower cranial nerves [11,12]. In our study, all the patients picked up quickly except one with HuntHess grade IV and no operating-related complications occurred, which is corresponded with other reports.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Recently, there are lots of reports regarding the interventional therapy of the artery aneurysms (including proximal and distal), all of which are considered to be safe and effective. All the incidences of interventional-related complications are below 10% and there is no report of injury of lower cranial nerves [11,12]. In our study, all the patients picked up quickly except one with HuntHess grade IV and no operating-related complications occurred, which is corresponded with other reports.…”
Section: Discussionsupporting
confidence: 89%
“…According to Nussbam's report [16], blocking the medullary velum and the distal of PICA can induce neither the ischemia of brainstem nor the cerebellum infarct. In Lim's study [12], all the five cases were treated using the aneurysm and parent artery aneurysm occlusion, and no ischemia of brainstem occurred. In our study, 4 cases (3 tonsillomedullary cases and 1 medullary velum case) were treated with the same method and no ischemia of medulla oblongata occurred in both the immediately postoperative interview and follow up.…”
Section: Discussionmentioning
confidence: 99%
“…22 In patients with a larger PICA, sacrificing the vessel may develop severe cerebellar edema. Trivelato et al 2 compared selective coiling and PVO for treatment of isolated PICA dissecting aneurysms, and they concluded that PVO was significantly associated with higher risk of ischemia and only 1 patient treated with selective coiling developed aneurysm recurrence.…”
Section: H LI Et Almentioning
confidence: 99%
“…When the vessel wall dissection extends through all layers they can cause a subarachnoid hemorrhage. These aneurysms have a high risk of rebleeding, necessitating expeditious treatment, usually by complete parent vessel occlusion (PVO) [5][6][7].…”
Section: Introductionmentioning
confidence: 99%